"Libraries from libraries": chemical transformation of combinatorial libraries to extend the range and repertoire of chemical diversity. - Ostresh, J M (1994)
The generation of diverse chemical libraries using a "libraries from libraries" concept is described. The central features of the approaches presented are the use of well-established solid-phase synthesis methods for the generation of combinatorial libraries, combined with the chemical transformation of such libraries while they remain attached to the solid support. The chemical libraries that are generated by this process have very different physical, chemical, and biological properties compared to the libraries from which they were derived. A wide range of chemical transformations are possible for peptide-based or other libraries, and an almost unlimited range of useful chemical diversities can be envisioned. In the example presented, the amide functionalities in an existing combinatorial library made up of peptides were permethylated while the library remained attached to the solid-phase support used in its synthesis. After removal of the permethylated mixtures from their solid support, this library, now lacking the typical -CONH- amide bonds of peptides, can be tested in solution with virtually all existing assay systems to identify individual compounds having specific biological activities of interest. An illustration of the use of such libraries is presented, in which the described permethylated library was used to identify individual permethylated compounds having potent antimicrobial activity against Gram-positive bacteria.